The effects of soft cryotherapy on conjunctiva and cornea in isolated pig eyes and comparison with standard liquid nitrogen: A pilot ex vivo study. (10th March 2020) - Barachetti, Laura; Giudice, Chiara; Cescon, Margherita; Mortellaro, Carlo M.; Ferrari, Roberta; Rampazzo, Antonella
Abstract: Purpose: To evaluate the immediate effects on cornea and conjunctiva of a cryosurgical method based on the application of a dimethyl ether, propane and isobutene solution (DMEPI, Histofreezer ® ), and of Liquid Nitrogen (LN2 ; Cry‐Ac Cryogun ® ). Methods: A total of 52 isolated pig eyes were obtained at the slaughterhouse, preserved for less than one hour in Ringer Lactate and divided into four groups. The first group included eyes treated with two applications of DMEPI in the center of the cornea, the second group eyes treated with DMEPI on the third eyelid's conjunctiva, the third group eyes treated with LN2 on the third eyelid's conjunctiva and the fourth group included eyes treated with LN2 on the central cornea. Each cryogen application (0.8 cm area) lasted 40 seconds. Each group included one (untreated) control eye. The eyes were submitted for routine histopathological evaluation. Histological alterations were recorded and scored with a semiquantitative scoring system. Results: No tissue alteration was detected on the conjunctiva, in any of the groups. Treated corneas showed mild to moderate cytoplasmic vacuolization of epithelial cells, shrinkage and hypereosinophilia of small groups of basal epithelial cells and stromal cleft formation. Conclusions: Soft cryosurgery caused no severe acute histologically detectable damage to cornea and conjunctiva in isolated pig eyes, and no significant difference was observed when LN2 and DMEPI treatments were compared. Further in vivo studies should be performed in order to verify possible delayed effects and the clinical efficacy of DMEPI cryosurgery in specific corneal and/or conjunctival diseases.